Materials and processing technology III : special topic volume with invited peer reviewed papers only - Chinakhov, D. A. (Diffusion and defect data. Solid state phenomena, 2020)
Intensive development of engineering contributes to the emergence of new materials and technologies for their processing. This special issue contains research papers on modern technologies for obtaining and processing materials, technologies for obtaining welded joints, additive technologies, technologies for engineering tasks in mechanical engineering and materials science. The book is intended for a wide range of specialists engaged in the development and production of heavy-duty metal structures, as well as students, undergraduates, graduate and postgraduate students of technical colleges and universities. Steel, Alloys, Ceramics, Tribology, Coatings, Surface Engineering, Welding, Electric Arc Deposition, Martensite Transformation, Laser Welding, Cladding, Friction Stir Welding, Elasto-Plastic Deformation, Internal Stress Materials Science, Mechanical Engineering, Manufacturing.